Convergent and criterion validity of PROMIS anxiety measures relative to six legacy measures and a structured diagnostic interview for anxiety in cancer patients - Kerrie Clover; Sylvie D. Lambert; Christopher Oldmeadow; Benjamin Britton; Alex J. Mitchell; Gregory Carter; Madeleine T. King (Journal of Patient-Reported Outcomes, 2022)
Abstract Background Detecting anxiety in oncology patients is important, requiring valid yet brief measures. One increasingly popular approach is the Patient Reported Outcomes Measurement Information System (PROMIS); however, its validity is not well established in oncology. We assessed the convergent and criterion validity of PROMIS anxiety measures in an oncology sample. Methods 132 oncology/haematology outpatients completed the PROMIS Anxiety Computer Adaptive Test (PROMIS-A-CAT) and the 7 item (original) PROMIS Anxiety Short Form (PROMIS-A-SF) along with six well-established measures: Hospital Anxiety and Depression Scale-Anxiety (HADS-A); Generalised Anxiety Disorder-7 (GAD-7); Depression, Anxiety and Stress Scale-Anxiety (DASS-A) and Stress (DASS-S); Distress Thermometer (DT) and PSYCH-6. Correlations, area under the curve (AUC) and diagnostic accuracy statistics were calculated with Structured Clinical Interview as the reference standard. Results Both PROMIS measures correlated with all legacy measures at p < .001 (Rho = .56–.83). AUCs (> .80) were good for both PROMIS measures and comparable to or better than all legacy measures. At the recommended mild cut-point (55), PROMIS-A-SF had sensitivity (.67) comparable to or better than all the legacy measures, whereas PROMIS-A-CAT sensitivity (.59) was lower than GAD-7 (.67) and HADS-A (.62), but comparable to PSYCH-6 and higher than DASS-A, DASS-S and DT. Sensitivity for both was .79. A reduced cut-point of 51 on both PROMIS measures improved sensitivity (.83–.84) although specificity was only adequate (.61–.62). Conclusions The convergent and criterion validity of the PROMIS anxiety measures in cancer populations was confirmed as equivalent, but not superior to, established measures (GAD-7 and HADS-A). The PROMIS-A-CAT did not demonstrate clear advantages over PROMIS-A-SF.